Broiler litter reutilization applying different composting concepts - Sonoda, LT (2012)
Broiler litter reutilization consists in using the same bedding material to cover the house floor for several broiler flocks. This requires the litter to be treated in order to reduce the amount of microorganisms, according to international recommendations. The aim of this study was to evaluate two methods of broiler litter fermentation based on composting concepts and their effect on litter and the air quality during fermentation in small-scale broiler houses. The experiment was carried out in the Environmental Laboratory I of the School of Agricultural Engineering of the State University of Campinas, utilizing six small-scale houses. Litter from the same grow-out (one, two or three) was distributed in two experimental houses, where it was either piled or spread. Before beginning the treatment, six litter samples were collected from each house and analyzed for total nitrogen content, humidity, pH and microbial counts. Litter humidity, gas emission (NH3 and CO2), environmental temperature, air relative humidity, and air velocity were determined during and after composting. Bacterial population, especially of Salmonella sp, was higher when the litter was piled compared with spread litter. However, fungi population showed a different pattern, decreasing after composting. Nevertheless, both treatments were not able to significantly reduce bacterial counts, specifically Salmonella sp, when the population before and after fermentation were compared